A chip off the (im)moral block? Lay beliefs about genetic heritability predicts whether family members' actions affect self‐judgments. (12th November 2021) - Peetz, Johanna; Wohl, Michael J. A.; Wilson, Anne E.; Dawson, Andrew
Abstract: The idea of heritability may have consequences for individuals' sense of self by connecting identity to the actions of others who happen to share genetic ties. Across seven experimental studies (total N = 2, 628), recalling morally bad or good actions by family members influenced individuals' moral self among those who endorse a lay belief that moral character is genetically heritable, but not among those who did not endorse this belief (Study 1–5). In contrast, recalling actions by unrelated individuals had no effect, regardless of lay beliefs (Study 2, 5), the endorsement of other relevant lay beliefs did not moderate the effect of parent's actions on self‐judgments (Study 3). Individuals who endorsed heritability beliefs also chose less helpful responses to hypothetical helping scenarios if they had recalled unhelpful (vs. helpful) acts by a genetically related family member (Study 5). Taken together, these studies suggest that lay beliefs in the role of genetics are important for self‐perceptions.